2019
DOI: 10.1097/rli.0000000000000525
|View full text |Cite
|
Sign up to set email alerts
|

Individually Body Weight–Adapted Contrast Media Application in Computed Tomography Imaging of the Liver at 90 kVp

Abstract: Objectives:The aim of the present study was to evaluate the attenuation and image quality (IQ) of a body weight-adapted contrast media (CM) protocol compared with a fixed injection protocol in computed tomography (CT) of the liver at 90 kV. Materials and Methods: One hundred ninety-nine consecutive patients referred for abdominal CT imaging in portal venous phase were included. Group 1 (n = 100) received a fixed CM dose with a total iodine load (TIL) of 33 g I at a flow rate of 3.5 mL/s, resulting in an iodine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 41 publications
1
35
0
1
Order By: Relevance
“…It typically consists of a multiphase acquisition including a noncontrast, arterial, and delayed phase of enhancement. 5 Some recent studies suggested the use of low tube voltages for singleenergy CTA (low-kV SEI) 6 because low-kV SEI increases the CT attenuation and contrast-to-noise ratio (CNR) in structures containing iodine 7 and is associated with less radiation dose. 8,9 With the introduction of dual-energy CT (DECT), further alternatives to improve iodine attenuation and to decrease radiation dose have become clinically available.…”
mentioning
confidence: 99%
“…It typically consists of a multiphase acquisition including a noncontrast, arterial, and delayed phase of enhancement. 5 Some recent studies suggested the use of low tube voltages for singleenergy CTA (low-kV SEI) 6 because low-kV SEI increases the CT attenuation and contrast-to-noise ratio (CNR) in structures containing iodine 7 and is associated with less radiation dose. 8,9 With the introduction of dual-energy CT (DECT), further alternatives to improve iodine attenuation and to decrease radiation dose have become clinically available.…”
mentioning
confidence: 99%
“…Future prospective studies could investigate the impact of personalised dosing on liver enhancement and diagnostic properties, which should also take tube voltage into account [14]. Many studies already investigated the potential of low kVp settings (e.g., 70, 80, and 100 kVp) [2,14,[29][30][31][32] or virtual monochromatic imaging with low kV reconstruction [33][34][35][36][37] in combination with a reduced amount of injected iodine in a more lightweight population using CT angiography protocols, wherein only the signal during the first pass of contrast media is crucial [29]. However, this has not properly been investigated for abdominal protocols yet, which rely on longer contrast media boluses to provide homogeneous enhancement of parenchymal organs, such as the liver.…”
Section: Discussionmentioning
confidence: 99%
“…A personalised protocol for iodine dosing should be preferred to the standard fixed-contrast protocol [13]. In this respect, body-weight-adapted contrast injection protocols have proven successful in achieving a more homogeneous enhancement of vascular structures and liver parenchyma in patients [8,[14][15][16][17]. However, total body weight (TBW) is not the only relevant body-size-related factor; lean body weight (LBW) and body mass index (BMI) might also be important.…”
Section: Introductionmentioning
confidence: 99%
“…The methods described above 22,24 are applicable for abdominal CT protocols with a single tube voltage (120 kV) only; however, recent approaches aim toward abdominal CT scanning with lower tube voltages. 36 In addition, these methods do not allow taking alternative scan lengths and body regions into account. In contrast, our approach allows for radiation dose assessments from any scanned body region, scan length, and CT protocol.…”
Section: Discussionmentioning
confidence: 99%